CoPi loaded dendrite (GaN) 1-x (ZnO) x -GaN nanowire array photoanode and preparation method

By growing (GaN)1-x(ZnO)x solid solution nanowires on GaN nanowire arrays and branching and loading CoPi oxygen evolution cocatalysts, the existing photoelectrodes are solved and the growth of existing photoelectrodes at high temperatures and The problem of insufficient binding force improves photoelectrocatalytic activity and efficiency.

CN115710716BActive Publication Date: 2025-01-03NORTHEASTERN UNIV FOSHAN GRADUATE SCHOOL OF INNOVATION +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211527116.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-01-03
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The thin film structure of the existing (GaN) 1-x(ZnO) x solid solution photoelectrode has problems such as fragile binding force, limited specific surface area, large contact resistance, and affecting photocatalytic activity and efficiency. The traditional conductive electrode is not suitable at high temperatures. .

Method used

The photoanode of the branched (GaN) 1-x(ZnO) x-GaN nanowire array was used to load a CoPi-loaded branched (GaN) 1-x(ZnO) x-GaN nanowire array was grown by chemical vapor deposition using Si-doped GaN single wafer as the substrate. And (GaN) 1-x(ZnO)x solid solution nanowire branches are grown on it, and CoPi oxygen evolution promoter is supported to form a three-dimensional dendritic structure to improve light absorption and electron transfer efficiency.

Benefits of technology

The photoelectrocatalytic activity and light absorption efficiency are improved, the problem of traditional photoelectrode growth at high temperatures is solved, the specific surface area is increased, the defect density and interface combination quality are reduced, and the efficient photoelectrocatalytic decomposition of water is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115710716B_ABST
    Figure CN115710716B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of semiconductor nanomaterials and photoelectrocatalytic water decomposition, and in particular to a dendritic (GaN) CoPi-loaded 1‑x (ZnO) x ‑GaN nanowire array photoanode and preparation method. The photoanode uses n-type Si doped GaN single crystal with good conductivity as substrate, homoepitaxially grows GaN nanowire array on the substrate by one-step chemical vapor deposition, and then grows (GaN) by one-step chemical vapor deposition with catalyst-assisted growth as the main trunk. 1‑x (ZnO) x The solid solution nanowires are branched and loaded with oxygen evolution promoter CoPi. The use of high temperature resistant and conductive n-type GaN substrates can not only meet the requirements of epitaxial growth of high crystalline quality GaN nanowire array materials under high temperature conditions, but also provide good interface contact and bonding between the GaN nanowire array and the GaN substrate, making it easy to transfer charges and can be applied to photoelectrocatalytic water decomposition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of semiconductor nanomaterials and photocatalytic water splitting, and particularly relates to a dendritic (GaN) loaded with cobalt phosphate (CoPi) 1-x (ZnO) x -GaN nanowire array photoanode, a preparation method thereof, and an application thereof in photocatalytic water splitting. Background Art

[0002] Solar energy is rich in reserves and widely distributed, and it is one of the most competitive clean energies. If the efficient utilization of solar energy can be achieved, it is expected to replace traditional fossil fuels. The use of semiconductor photoanodes to split water to produce clean hydrogen fuel has always attracted much attention and is considered to be one of the effective ways to solve future energy crises and sustainable development. In 2005, the Domen research group at the University of Tokyo, Japan, first solid-solved two semiconductors, GaN and ZnO, to prepare a (GaN) 1-x (ZnO) x solid solution (0.034 < x < 0.13), and by regulating the content of ZnO in the solid solution, the band gap of the solid solution was regulated and visible-light photocatalytic water splitting to produce hydrogen was achieved. Thereafter, researchers found that (GaN) 1-x (ZnO) x solid solution also shows great potential in the field of photocatalytic water splitting.

[0003] However, the currently studied (GaN) 1-x (ZnO) x solid solution photoanodes are mainly thin-film electrodes, and mostly the (GaN) 1-x (ZnO) x solid solution is mixed with an adhesive and then coated on the surface of the substrate. The bonding force is very weak and it is easy to fall off, affecting the life and stability; moreover, its specific surface area is very limited, which limits the photocatalytic active area and the light absorption efficiency. In addition, for this kind of coated and sintered (GaN) 1-x (ZnO) x solid solution thin-film photoelectrodes, the contact between the solid solution powders and the contact with the collector are weak, the contact resistance is large, making the transfer of photogenerated electrons difficult, and the recombination ratio of photogenerated electron-hole pairs inside the catalyst increases, affecting the photoelectric conversion efficiency. At the same time, the too large contact resistance will cause a large voltage drop, making the effective voltage actually loaded on the catalyst very limited. In addition, (GaN) 1-x (ZnO) xThe preparation of quaternary solid solution nanomaterials involves the substitution of four elements, Ga, Zn, O, and N, which makes the preparation process complex and difficult. Especially at higher preparation temperatures, the traditional FTO conductive electrode is easy to decompose and is no longer suitable as a collector. It is necessary to find a transparent electrode that is resistant to high temperature and has a thermal expansion coefficient close to that of (GaN) 1-x (ZnO) x Growth of solid solution nanomaterials. Summary of the invention

[0004] Based on the above problems, the object of the present invention is to provide a dendritic (GaN) 1-x (ZnO) x -GaN nanowire array photoanode and preparation method, the GaN nanowires prepared by this method have good crystal quality and good interface contact and bonding with the conductive GaN substrate. The GaN substrate not only has good conductivity, which can meet the transfer of photogenerated electrons, but also can withstand high temperatures, which can meet the high-temperature growth of GaN nanowire array materials. The secondary growth (GaN) 1-x (ZnO) x The solid solution nanowire branching greatly increases the specific surface area of ​​the catalyst and improves the light absorption efficiency. 1-x (ZnO) x The conduction band positions of the two are close, and it is not easy to form a high Schottky barrier at the interface, which facilitates the rapid transfer of photogenerated electrons.

[0005] The present invention adopts the following technical solution:

[0006] A CoPi-loaded dendrite (GaN) 1-x (ZnO) x -GaN nanowire array photoanode, CoPi loaded dendrite (GaN) 1-x (ZnO) x -GaN nanowire array photoanode uses n-type Si doped GaN single crystal with good conductivity as substrate, the main trunk is GaN nanowire array, and the branches are (GaN) 1-x (ZnO) x Solid solution nanowires, the solid solubility of ZnO is 19.4at%.

[0007] The CoPi loaded dendrite (GaN) 1-x (ZnO) x -GaN nanowire array photoanode, the GaN substrate used is a Si-doped n-type GaN single crystal prepared by MOCVD technology, the film thickness is 4 to 6μm, and the square resistance is 14.08kΩ / □.

[0008] The CoPi loaded dendrite (GaN)1-x (ZnO) x -GaN nanowire array photoanode, the GaN nanowire array material is epitaxially grown by chemical vapor deposition, the diameter of a single GaN nanowire is between 100 and 150 nm, and the length is between 10 and 25 μm.

[0009] The CoPi loaded dendrite (GaN) 1-x (ZnO) x -GaN nanowire array photoanode, dendrites grown on GaN nanowires (GaN) 1-x (ZnO) x The diameter of the solid solution nanowires is between 15 and 25 nm, and the length is between 200 and 300 nm.

[0010] The CoPi loaded dendrite (GaN) 1-x (ZnO) x -GaN nanowire array photoanode, which exhibits a typical three-dimensional dendrite structure, with GaN nanowires grown on the trunk (GaN) 1-x (ZnO) x Solid solution nanowire branching, (GaN) 1-x (ZnO) x CoPi oxygen evolution co-catalyst supported on solid solution nanowire branches, (GaN) 1-x (ZnO) x Au particles are deposited on the top of the solid solution nanowire branches.

[0011] The CoPi loaded dendrite (GaN) 1-x (ZnO) x - A method for preparing a GaN nanowire array photoanode, which is divided into four stages and includes the following steps:

[0012] In the first stage, GaN nanowire arrays are grown on n-type Si-doped GaN single crystal wafers:

[0013] (1) Weigh 30-50 mL of deionized water and pour it into a reactor, add 0.5-1.5 mL of 3-5 mg / mL HAuCl4 solution and 2-4 mL of methanol CH3OH and stir evenly; then place the n-type Si-doped GaN single crystal substrate into the obtained solution, evacuate the reactor, and irradiate the top of the substrate with a 300 W xenon lamp for 10-30 min; take it out and wash it with deionized water, and then blow dry it with high-purity N2;

[0014] (2) Weigh gallium oxide Ga2O3 powder and evenly spread it on the bottom of the alumina porcelain boat, invert the substrate obtained in step (1) on top of the porcelain boat containing gallium oxide Ga2O3 powder, and place it in a single temperature zone tubular furnace;

[0015] (3) The tubular furnace is evacuated to a vacuum state, and then Ar gas is introduced to normal pressure, with an Ar gas flow rate of 40 to 60 sccm; the tubular furnace is heated at a rate of 10 to 15°C / min, and when the temperature reaches 800 to 900°C, the Ar gas is turned off, and NH3 is introduced at a gas flow rate of 10 to 100 sccm;

[0016] (4) When the tube furnace reaches the reaction temperature, the reaction is fully reacted and then cooled naturally to obtain a GaN nanowire array material with an n-type Si-doped GaN single crystal wafer having good conductivity as a substrate;

[0017] The second stage is to prepare Zn-Ga-O precursor powder:

[0018] (5) Weigh zinc acetate dihydrate Zn(CH3COO)2·2H2O and hydrated gallium nitrate Ga(NO3)3·xH2O, and place them in a 50 mL beaker, wherein the atomic ratio of Zn to Ga in the zinc acetate dihydrate and the hydrated gallium nitrate is 5:5, and the total weight of the powder is 4 to 6 g;

[0019] (6) Add 15-25 mL of ethylene glycol methyl ether (C3H8O2) and 0.5-1.5 mL of ethanolamine (C2H7NO) to step (5), and stir until the powder is completely dissolved;

[0020] (7) placing the solution obtained in step (6) in a water bath at 60-80° C. and stirring and heating for 5-7 h to obtain a sol, and then taking it out and letting it stand for one week to obtain a gel;

[0021] (8) pouring the gel obtained in step (7) into an alumina porcelain boat and placing it in a single temperature zone tube furnace, and air annealing at 450-550° C. for 1.5-2.5 h to obtain a Zn—Ga—O precursor powder;

[0022] The third stage is the growth of GaN nanowire arrays (GaN) 1-x (ZnO) x Solid solution nanowire branching:

[0023] (9) Weigh 30-50 mL of deionized water and pour it into a reactor, add 0.5-1.5 mL of 3-5 mg / mL chloroauric acid HAuCl4 solution, 2-4 mL of methanol CH3OH and 8-12 mg of polyvinyl pyrrolidone PVP and stir evenly; then put the GaN nanowire array obtained in step (4) into the solution, evacuate the reactor, and irradiate the top of the reactor with a 300 W xenon lamp for 10-30 min;

[0024] (10) Weigh the Zn—Ga—O precursor powder obtained in step (8) and place it in an alumina porcelain boat, and invert the sample obtained in step (9) on top of the porcelain boat containing the Zn—Ga—O precursor powder, and place it in a single-temperature zone tubular furnace;

[0025] (11) Before heating the tube furnace, purge the quartz tube with Ar gas for 20 to 40 minutes at a gas flow rate of 80 to 120 sccm, and then adjust the gas flow rate to 40 to 60 sccm;

[0026] (12) The heating rate of the tubular furnace is 10-15°C / min. When the temperature reaches 700-750°C, the Ar gas is turned off and NH3 is introduced at a flow rate of 50-100 sccm;

[0027] (13) When the tube furnace reaches the reaction temperature, it is kept warm for sufficient reaction and then cooled naturally to obtain dendritic (GaN) 1-x (ZnO) x / GaN nanowire array photoanode;

[0028] The fourth stage, in (GaN) 1-x (ZnO) x / GaN nanowire array / CoPi oxygen evolution co-catalyst loaded on GaN by light-assisted electrodeposition:

[0029] (14) preparing 80-120 mL of a phosphate buffer solution with a molar concentration of 0.05-0.15 M and a pH of 7, then adding 0.05-0.15 mL of a cobalt nitrate hexahydrate Co(NO3)2·6H2O solution with a molar concentration of 4-6 mM and stirring well, and pouring into the electrolytic cell;

[0030] (15) The sample obtained in step (13) was used as the working electrode, the Pt sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. The CoPi was loaded by the constant current method, the current was set to -10 μA, the deposition time was 5 to 30 min, and 80 to 120 mW / cm was used during the deposition. 2 The light source irradiates the sample surface;

[0031] (16) Take out the sample obtained in step (15), wash it with deionized water and dry it to obtain the dendritic (GaN) loaded with CoPi. 1-x (ZnO) x -GaN nanowire array photoanode.

[0032] The CoPi loaded dendrite (GaN) 1-x (ZnO) x -A method for preparing a GaN nanowire array photoanode, in step (2), the mass of gallium oxide weighed is 0.5 to 1.0 g.

[0033] The CoPi loaded dendrite (GaN) 1-x (ZnO) x-A method for preparing a GaN nanowire array photoanode, wherein in step (4), the reaction temperature is 1000-1150°C and the insulation time is 5-15 minutes.

[0034] The CoPi loaded dendrite (GaN) 1-x (ZnO) x -A method for preparing a GaN nanowire array photoanode, in step (10), 0.4 to 0.6 g of Zn-Ga-O precursor powder.

[0035] The CoPi loaded dendrite (GaN) 1-x (ZnO) x -A method for preparing a GaN nanowire array photoanode, wherein in step (13), the reaction temperature is 850-900°C and the insulation time is 5-20 minutes.

[0036] The design idea of ​​the present invention is:

[0037] Bandgap adjustable (GaN) 1-x (ZnO) x Solid solution nanowire arrays have excellent visible light absorption, suitable energy band structure, and wide spectral utilization range. They are a good material for photoelectrocatalytic water decomposition to produce hydrogen, but they require high temperature synthesis, and traditional conductive substrates (ITO, FTO, etc.) cannot meet the requirements of high temperature growth. The present invention proposes to use Si-doped GaN single crystals with good conductivity as substrates, homoepitaxially grow single crystal GaN nanowire arrays, and then grow three-dimensional dendrites (GaN) 1-x (ZnO) x / GaN nanowire array photoanode and co-catalyst CoPi. 1-x (ZnO) x The solid solution is the main photoelectrocatalytic active substance, which has a band structure suitable for complete water splitting and visible light activity, and produces multiple scattering through a unique dendrite morphology, thereby significantly improving the light absorption efficiency. In addition, through (GaN) 1-x (ZnO) x The type-Ⅱ heterojunction formed between the solid solution nanowires and GaN nanowires also greatly improves the separation efficiency of electrons and holes, while the conductive GaN substrate provides an excellent electron transmission channel.

[0038] The present invention has the following advantages and technical effects:

[0039] 1. The present invention adopts an n-type Si-doped GaN single crystal substrate with good conductivity (Si doping makes GaN have a high density of free electrons, thereby significantly improving the conductivity), which not only solves the problem of epitaxial growth of GaN nanowire array materials, but also forms a good coherent interface between the GaN nanowire array and the substrate to meet the transport problem of photogenerated carriers. At the same time, it solves the problem that the melting point of the traditional FTO conductive glass substrate is too low to meet the requirements of the GaN nanowire array and (GaN) 1-x (ZnO) x The high-temperature growth problem of solid solution nanowires was used to construct high-temperature conductive electrodes.

[0040] 2. The equipment used in the present invention is simple, easy to operate and has good repeatability.

[0041] 3. Dendritic (GaN) loaded with CoPi synthesized by the present invention 1-x (ZnO) x / GaN nanowire array photoanode has a large specific surface area, which is beneficial to improving the light absorption efficiency.

[0042] 4. Dendritic (GaN) loaded with CoPi synthesized by the present invention 1-x (ZnO) x The GaN / GaN nanowire array photoanode is grown heterogeneously, which reduces the defect density and improves the interface bonding quality, thereby enhancing its photoelectrocatalytic activity.

[0043] 5. Dendritic (GaN) loaded with CoPi synthesized by the present invention 1-x (ZnO) x The photoanode of the GaN nanowire array was loaded with CoPi oxygen evolution co-catalyst to improve its photoelectrocatalytic activity. The photoanode was applied to photoelectrocatalytic water decomposition. -2 Under simulated solar irradiation, the photocurrent density can reach 80 μA cm when the bias voltage is 1.23 V vs. RHE. -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The prepared CoPi loaded dendrite (GaN) 1-x (ZnO) x Schematic diagram of the GaN / GaN nanowire array photoanode.

[0045] In the figure, 1. Au particles, 2. CoPi oxygen evolution promoter, 3. (GaN) 1-x (ZnO) x Solid solution nanowire branches, 4. GaN nanowire trunk, 5. GaN epitaxial layer, 6. Sapphire substrate.

[0046] Figure 2The CoPi-loaded dendritic (GaN) prepared in Example 1 1-x (ZnO) x Scanning electron microscope (SEM) images of the GaN nanowire array photoanode. Figure a is a cross-sectional scanning image, and Figure b is a top scanning image.

[0047] Figure 3 The CoPi-loaded dendritic (GaN) prepared in Example 1 1-x (ZnO) x X-ray diffraction (XRD) pattern of GaN nanowire array photoanode.

[0048] Figure 4 The CoPi-loaded dendritic (GaN) prepared in Example 1 1-x (ZnO) x Energy dispersive X-ray spectroscopy (EDS) of GaN nanowire array photoanode. Figure a shows a single dendrite (GaN) 1-x (ZnO) x Figure 1 is a high-angle annular dark field image of Ga / GaN nanowires; Figure b is the element distribution map of Ga element; Figure c is the element distribution map of N element; Figure d is the element distribution map of Zn element; Figure e is the element distribution map of O element; Figure f is the element distribution map of Au element.

[0049] Figure 5 The CoPi-loaded dendritic (GaN) prepared in Example 1 1-x (ZnO) x (a) Transmission electron microscope (TEM) image and (b) high-resolution transmission electron microscope (HRTEM) image of GaN / GaN nanowire array photoanode. Figures a and b are TEM morphology images at different magnifications; Figure c is (GaN) 1-x (ZnO) x High-resolution TEM image of solid solution branches; Figure d is (GaN) 1-x (ZnO) x Selected area electron diffraction (SAED) pattern of solid solution branching.

[0050] Figure 6 The CoPi-loaded dendritic (GaN) prepared in Example 1 1-x (ZnO) x Ultraviolet-visible absorption spectrum (UV-vis) of GaN nanowire array photoanode.

[0051] Figure 7 The GaN nanowire array photoanode prepared in Example 1, the dendritic (GaN) 1-x (ZnO) x / GaN nanowire array photoanode and photoelectrocatalytic performance after loading CoPi. DETAILED DESCRIPTION

[0052] In the specific implementation process, the present invention proposes a dendritic (GaN) CoPi load 1-x (ZnO) x -GaN nanowire array photoanode, CoPi loaded dendrite (GaN) 1-x (ZnO) x -GaN nanowire array photoanode uses n-type Si doped GaN single crystal with good conductivity as substrate, the main trunk is GaN nanowire array, and the branches are (GaN) 1-x (ZnO) x Solid solution nanowires, the solid solubility of ZnO is 19.4at%. The GaN substrate used is a Si-doped n-type GaN single crystal prepared by MOCVD technology, the film thickness is 5μm, and the square resistance is 14.08kΩ / □. The GaN nanowire array material is epitaxially grown by chemical vapor deposition. The diameter of a single GaN nanowire is between 100 and 150nm, and the length is between 10 and 25μm. Dendritic (GaN) grown on GaN nanowires 1-x (ZnO) x The diameter of the solid solution nanowires is between 15 and 25 nm, and the length is between 200 and 300 nm.

[0053] The present invention will be further described below in conjunction with the accompanying drawings and Examples. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, after reading the content of the present invention, those skilled in the art may change or modify the present invention without departing from the spirit of the appended claims and the scope of the present invention.

[0054] Embodiment 1:

[0055] In this embodiment, the dendritic (GaN) loaded by CoPi 1-x (ZnO) x The preparation method of GaN nanowire array photoanode, the specific steps are as follows:

[0056] (1) Weigh 40 mL of deionized water and pour it into the reactor. Add 1 mL of 4 mg / mL HAuCl4 solution and 3 mL of methanol CH3OH and stir evenly. Then put the n-type Si-doped GaN single crystal substrate into the solution. After the reactor is evacuated, irradiate the top with a 300W xenon lamp for 30 minutes. After taking it out, wash it with deionized water and then blow it dry with high-purity N2 (volume purity 99.999%).

[0057] (2) Weigh 0.8 g of gallium oxide Ga2O3 powder (short rod-shaped powder with a diameter of about 1 to 5 μm and a length of 1 to 15 μm) and evenly spread it on the bottom of the alumina porcelain boat, invert the substrate obtained in step (1) on top of the porcelain boat containing gallium oxide Ga2O3 powder, and place it in a single-temperature zone tubular furnace;

[0058] (3) The tube furnace was evacuated to vacuum, and then Ar gas was introduced to atmospheric pressure, with an Ar gas flow rate of 50 sccm. The tube furnace was heated at a rate of 10°C / min. When the temperature reached 800°C, the Ar gas was turned off and NH3 was introduced at a gas flow rate of 50 sccm;

[0059] (4) When the tube furnace reaches 1150° C., the tube furnace is kept at this temperature for 10 minutes and then cooled naturally to obtain a GaN nanowire array with an n-type Si-doped GaN single crystal wafer as the substrate;

[0060] (5) Weigh zinc acetate dihydrate Zn(CH3COO)2·2H2O and hydrated gallium nitrate Ga(NO3)3·xH2O, and place them in a 50 mL beaker, wherein the atomic ratio of Zn to Ga in zinc acetate dihydrate and hydrated gallium nitrate is 5:5, and the total weight of the powder is 4.8 g; wherein zinc acetate dihydrate is in the form of flakes or plate-like crystals, and hydrated gallium nitrate is in the form of blocks;

[0061] (6) Add 20 mL of ethylene glycol methyl ether (C3H8O2) and 1 mL of ethanolamine (C2H7NO) to step (5) and stir until the powder is completely dissolved;

[0062] (7) placing the solution obtained in step (6) in a water bath and stirring and heating at 70° C. for 6 h to obtain a sol, and then taking it out and letting it stand for one week to obtain a gel;

[0063] (8) pouring the gel obtained in step (7) into an alumina porcelain boat and placing it in a single temperature zone tube furnace, and annealing in air at 500° C. for 2 h to obtain a Zn—Ga—O precursor powder with a particle size of 30 to 50 nm;

[0064] (9) Weigh 40 mL of deionized water and pour it into the reactor, add 1 mL of 4 mg / mL HAuCl4 solution, 3 mL of methanol CH3OH and 10 mg of polyvinyl pyrrolidone PVP and stir evenly. Then put the GaN nanowire array obtained in step (4) into the solution, evacuate the reactor, and irradiate the top with a 300 W xenon lamp for 30 min;

[0065] (10) Weigh 0.5 g of the Zn—Ga—O precursor powder obtained in step (8) and place it in an alumina porcelain boat, and invert the sample obtained in step (9) on top of the porcelain boat containing the Zn—Ga—O precursor powder, and place it in a single-temperature zone tubular furnace;

[0066] (11) Before heating the tube furnace, the quartz tube was cleaned with Ar gas for 30 min at a gas flow rate of 100 sccm, and then the gas flow rate was adjusted to 50 sccm;

[0067] (12) The heating rate of the tubular furnace was 10 °C / min. When the temperature reached 700 °C, the Ar gas was turned off and NH3 was introduced at a flow rate of 50 sccm;

[0068] (13) When the tube furnace reaches 900°C, keep it warm for 10 minutes and then cool it naturally to obtain dendritic (GaN) 1-x (ZnO) x / GaN nanowire array photoanode;

[0069] (14) preparing 100 mL of phosphate buffer with a molar concentration of 0.1 M and a pH of 7, then adding 1 mL of a 5 mM cobalt nitrate hexahydrate Co(NO3)2·6H2O solution thereto and stirring well, and then pouring the mixture into the electrolytic cell;

[0070] (15) The sample obtained in step (13) was used as the working electrode, the Pt sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. The CoPi was loaded by the constant current method. The current was set to -10 μA, the deposition time was 10 min, and 100 mW / cm was used during the deposition. 2 The light source irradiates the sample surface;

[0071] (16) Take out the sample obtained in step (15), wash it with deionized water and dry it to obtain the dendritic (GaN) loaded with CoPi. 1-x (ZnO) x / GaN nanowire array photoanode.

[0072] like Figure 1 As shown, the GaN epitaxial layer 5 (GaN substrate) is stacked on the sapphire substrate 6, and a GaN nanowire array is epitaxially grown on the GaN epitaxial layer 5. The dendrite (GaN) loaded by CoPi 1-x (ZnO) x / GaN nanowire array photoanode presents a typical three-dimensional dendrite structure, with GaN nanowires grown on the trunk 4 (GaN) 1-x (ZnO) x Solid solution nanowire branch 3, (GaN) 1-x (ZnO) x CoPi oxygen evolution promoter 2 loaded on solid solution nanowire branch 3, (GaN) 1-x (ZnO) x Au particles 1 are deposited on top of the solid solution nanowire branches 3 .

[0073] like Figure 2As shown, the dendritic (GaN) loaded by CoPi in this embodiment is imaged by SEM. 1-x (ZnO) x / GaN nanowire array photoanode morphology was observed. The dendritic (GaN) 1-x (ZnO) x / GaN nanowire array photoanode presents a typical three-dimensional dendritic structure, and the GaN nanowire array and GaN substrate, GaN nanowire array and (GaN) 1-x (ZnO) x The solid solution nanowires have good interface bonding.

[0074] like Figure 3 As shown, the dendritic (GaN) loaded by CoPi in this embodiment is analyzed by XRD. 1-x (ZnO) x / GaN nanowire array photoanode crystal structure was characterized, the CoPi loaded dendrite (GaN) 1-x (ZnO) x The GaN / GaN nanowire array photoanode is a single-phase material without impurity phase.

[0075] like Figure 4 As shown, the dendrites (GaN) of the CoPi load of this embodiment are analyzed by EDS. 1-x (ZnO) x / GaN nanowire array photoanode composition analysis, the CoPi loaded dendrite (GaN) 1-x (ZnO) x The GaN / GaN nanowire array photoanode contains only five elements: Zn, Ga, O, N and Au. The trunk is mainly composed of Ga and N elements, and the branches are mainly composed of Zn, Ga, O, N and Au at the top.

[0076] like Figure 5 As shown, the dendritic (GaN) loaded by CoPi in this embodiment is characterized by TEM, HRTEM and SAED. 1-x (ZnO) x / GaN nanowire array photoanode microstructure analysis, the CoPi loaded dendrite (GaN) 1-x (ZnO) x / GaN nanowire array photoanode shows a typical dendritic structure, with the main GaN nanowire and branches (GaN) 1-x (ZnO) x The surface of the solid solution nanowires is covered with a CoPi layer about 10 nm thick, the trunk and branches are well crystallized, and the branches show a typical hexagonal structure.

[0077] like Figure 6 As shown, the dendritic (GaN) loaded by CoPi in this embodiment is analyzed by UV-vis spectroscopy. 1-x (ZnO) x / GaN nanowire array photoanode diffuse reflectance spectrum analysis, the CoPi loaded dendrite (GaN) of this embodiment 1-x (ZnO) x Compared with pure GaN nanowires, the absorption band edge of the GaN / GaN nanowire array photoanode extends from the ultraviolet region to the infrared region, improving the utilization of the spectrum.

[0078] like Figure 7 As shown, the dendritic (GaN) loaded by CoPi of this embodiment is tested by a photoelectrocatalytic test system. 1-x (ZnO) x The photoelectrocatalytic water splitting performance of the GaN nanowire array photoanode was tested (the electrolyte was a 0.5 M Na2SO4 aqueous solution). -2 Under simulated solar irradiation, the photocurrent density can reach 186μA·cm at an applied bias of 1.23V vs.RHE. -2 The present invention is different from pure GaN nanowire array photoanode and dendritic (GaN) 1-x (ZnO) x / GaN nanowire array photoanode, its photocurrent density is significantly improved.

[0079] Embodiment 2:

[0080] In this embodiment, the dendritic (GaN) loaded by CoPi 1-x (ZnO) x The preparation method of GaN nanowire array photoanode, the specific steps are as follows:

[0081] (1) Weigh 40 mL of deionized water and pour it into the reactor. Add 1 mL of 4 mg / mL HAuCl4 solution and 3 mL of methanol CH3OH and stir evenly. Then put the n-type Si-doped GaN single crystal substrate into the solution. After the reactor is evacuated, irradiate the top with a 300W xenon lamp for 30 minutes. After taking it out, wash it several times with deionized water, and then blow it dry with high-purity N2 (volume purity 99.999%);

[0082] (2) Weigh 0.8 g of gallium oxide Ga2O3 powder (powder diameter is about 1-5 μm, length is 1-15 μm) and spread it evenly on the bottom of the alumina porcelain boat, invert the substrate obtained in step (1) on the porcelain boat containing gallium oxide Ga2O3 powder, and put it into a single temperature zone tubular furnace;

[0083] (3) The tube furnace was evacuated to vacuum, and then Ar gas was introduced to atmospheric pressure, with an Ar gas flow rate of 50 sccm. The tube furnace was heated at a rate of 10°C / min. When the temperature reached 800°C, the Ar gas was turned off and NH3 was introduced at a gas flow rate of 100 sccm;

[0084] (4) When the tube furnace reaches 1150° C., the temperature is maintained for 5 minutes and then cooled naturally to obtain a GaN nanowire array with an n-type Si-doped GaN single crystal wafer as the substrate;

[0085] (5) Weigh zinc acetate dihydrate Zn(CH3COO)2·2H2O and hydrated gallium nitrate Ga(NO3)3·xH2O, and place them in a 50 mL beaker, wherein the atomic ratio of Zn to Ga in zinc acetate dihydrate and hydrated gallium nitrate is 5:5, and the total weight of the powder is 4.8 g; wherein zinc acetate dihydrate is in the form of flakes or plate-like crystals, and hydrated gallium nitrate is in the form of blocks;

[0086] (6) Add 20 mL of ethylene glycol methyl ether (C3H8O2) and 1 mL of ethanolamine (C2H7NO) to step (5) and stir until the powder is completely dissolved;

[0087] (7) placing the solution obtained in step (6) in a water bath and stirring and heating at 70° C. for 6 h to obtain a sol, and then taking it out and letting it stand for one week to obtain a gel;

[0088] (8) pouring the gel obtained in step (7) into an alumina porcelain boat and placing it in a single temperature zone tube furnace, annealing in air at 500° C. for 2 h to obtain a Zn—Ga—O precursor powder with a powder particle size of 30 to 50 nm;

[0089] (9) Weigh 40 mL of deionized water and pour it into the reactor, add 1 mL of 4 mg / mL HAuCl4 solution, 3 mL of methanol CH3OH and 10 mg of polyvinyl pyrrolidone PVP and stir evenly. Then put the GaN nanowire array obtained in step (4) into the solution, evacuate the reactor, and irradiate the top with a 300 W xenon lamp for 30 min;

[0090] (10) Weigh 0.5 g of the Zn—Ga—O precursor powder obtained in step (8) and place it in an alumina porcelain boat, and invert the sample obtained in step (9) on top of the porcelain boat containing the Zn—Ga—O precursor powder, and place it in a single-temperature zone tubular furnace;

[0091] (11) Before heating the tube furnace, the quartz tube was cleaned with Ar gas for 30 min at a gas flow rate of 100 sccm, and then the gas flow rate was adjusted to 50 sccm;

[0092] (12) The heating rate of the tubular furnace was 10 °C / min. When the temperature reached 700 °C, the Ar gas was turned off and NH3 was introduced at a flow rate of 50 sccm;

[0093] (13) When the tube furnace reaches 900°C, keep it warm for 10 minutes and then cool it naturally to obtain dendritic (GaN) 1-x (ZnO) x / GaN nanowire array photoanode;

[0094] (14) preparing 100 mL of phosphate buffer with a molar concentration of 0.1 M and a pH of 7, then adding 1 mL of a 5 mM cobalt nitrate hexahydrate Co(NO3)2·6H2O solution thereto and stirring well, and then pouring the mixture into the electrolytic cell;

[0095] (15) The sample obtained in step (13) was used as the working electrode, the Pt sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. The CoPi was loaded by the constant current method. The current was set to -10 μA, the deposition time was 20 min, and 100 mW / cm was used during the deposition. 2 The light source irradiates the sample surface;

[0096] (16) Take out the sample obtained in step (15), wash it with deionized water and dry it to obtain the dendritic (GaN) loaded with CoPi. 1-x (ZnO) x / GaN nanowire array photoanode.

[0097] The photoelectrocatalytic water splitting test results of this embodiment show that at 100 mW·cm -2 Under simulated solar irradiation, the photocurrent density can reach 84 μA cm at an applied bias of 1.23 V vs. RHE. -2 .

[0098] Embodiment 3:

[0099] In this embodiment, the dendritic (GaN) loaded by CoPi 1-x (ZnO) x The preparation method of GaN nanowire array photoanode, the specific steps are as follows:

[0100] (1) Weigh 40 mL of deionized water and pour it into the reactor. Add 1 mL of 4 mg / mL HAuCl4 solution and 3 mL of methanol CH3OH and stir evenly. Then put the n-type Si-doped GaN single crystal substrate into the solution. After the reactor is evacuated, irradiate the top with a 300W xenon lamp for 30 minutes. After taking it out, wash it several times with deionized water, and then blow it dry with high-purity N2 (volume purity 99.999%);

[0101] (2) Weigh 1.0 g of gallium oxide Ga2O3 powder (powder diameter is about 1-5 μm, length is 1-15 μm) and spread it evenly on the bottom of the alumina porcelain boat, invert the substrate obtained in step (1) on the porcelain boat containing gallium oxide Ga2O3 powder, and put it into a single temperature zone tubular furnace;

[0102] (3) The tube furnace was evacuated to vacuum, and then Ar gas was introduced to atmospheric pressure, with an Ar gas flow rate of 50 sccm. The tube furnace was heated at a rate of 10°C / min. When the temperature reached 800°C, the Ar gas was turned off and NH3 was introduced at a gas flow rate of 50 sccm;

[0103] (4) When the tube furnace reaches 1100° C., the temperature is maintained for 10 minutes and then cooled naturally to obtain a GaN nanowire array with an n-type Si-doped GaN single crystal wafer as the substrate;

[0104] (5) Weigh zinc acetate dihydrate Zn(CH3COO)2·2H2O and hydrated gallium nitrate Ga(NO3)3·xH2O, and place them in a 50 mL beaker, wherein the atomic ratio of Zn to Ga in zinc acetate dihydrate and hydrated gallium nitrate is 5:5, and the total weight of the powder is 4.8 g; wherein zinc acetate dihydrate is in the form of flakes or plate-like crystals, and hydrated gallium nitrate is in the form of blocks;

[0105] (6) Add 20 mL of ethylene glycol methyl ether (C3H8O2) and 1 mL of ethanolamine (C2H7NO) to step (5) and stir until the powder is completely dissolved;

[0106] (7) placing the solution obtained in step (6) in a water bath and stirring and heating at 70° C. for 6 h to obtain a sol, and then taking it out and letting it stand for one week to obtain a gel;

[0107] (8) pouring the gel obtained in step (7) into an alumina porcelain boat and placing it in a single temperature zone tube furnace, annealing in air at 500° C. for 2 h to obtain a Zn—Ga—O precursor powder with a powder particle size of 30 to 50 nm;

[0108] (9) Weigh 40 mL of deionized water and pour it into the reactor, add 1 mL of 4 mg / mL HAuCl4 solution, 3 mL of methanol CH3OH and 10 mg of polyvinyl pyrrolidone PVP and stir evenly. Then put the GaN nanowire array obtained in step (4) into the solution, evacuate the reactor, and irradiate the top with a 300 W xenon lamp for 30 min;

[0109] (10) Weigh 0.5 g of the Zn—Ga—O precursor powder obtained in step (8) and place it in an alumina porcelain boat, and invert the sample obtained in step (9) on top of the porcelain boat containing the Zn—Ga—O precursor powder, and place it in a single-temperature zone tubular furnace;

[0110] (11) Before heating the tube furnace, the quartz tube was cleaned with Ar gas for 30 min at a gas flow rate of 100 sccm, and then the gas flow rate was adjusted to 50 sccm;

[0111] (12) The heating rate of the tubular furnace was 10 °C / min. When the temperature reached 700 °C, the Ar gas was turned off and NH3 was introduced at a flow rate of 50 sccm;

[0112] (13) When the tube furnace reaches 900°C, keep it warm for 15 minutes and then cool it naturally to obtain dendritic (GaN) 1-x (ZnO) x / GaN nanowire array photoanode;

[0113] (14) preparing 100 mL of phosphate buffer with a molar concentration of 0.1 M and a pH of 7, then adding 1 mL of a 5 mM cobalt nitrate hexahydrate Co(NO3)2·6H2O solution thereto and stirring well, and then pouring the mixture into the electrolytic cell;

[0114] (15) The sample obtained in step (13) was used as the working electrode, the Pt sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. The CoPi was loaded by the constant current method. The current was set to -10 μA, the deposition time was 10 min, and 100 mW / cm was used during the deposition. 2 The light source irradiates the sample surface;

[0115] (16) Take out the sample obtained in step (15), wash it with deionized water and dry it to obtain the dendritic (GaN) loaded with CoPi. 1-x (ZnO) x / GaN nanowire array photoanode.

[0116] The photoelectrocatalytic water splitting test results of this embodiment show that at 100 mW·cm -2 Under simulated solar irradiation, the photocurrent density can reach 87μA·cm at an applied bias of 1.23V vs.RHE. -2 .

[0117] The results of the embodiment show that the dendritic (GaN) loaded by the CoPi 1-x (ZnO) x The GaN nanowires in the GaN nanowire array photoanode have good crystal quality and have good interface contact and bonding strength with the substrate. The use of a GaN single crystal substrate with good conductivity not only solves the problem of epitaxial growth of GaN nanowire array materials, but also forms a good coherent interface between the GaN nanowire array and the substrate to meet the transport problem of photogenerated carriers. At the same time, it also solves the problem that the traditional FTO conductive glass substrate has a low melting point and cannot meet the requirements of the GaN nanowire array and (GaN) 1-x (ZnO)x High temperature growth of solid solution nanowires to construct high temperature conductive electrodes. (GaN) 1-x (ZnO) x The solid solution nanowire branching greatly increases the specific surface area of ​​the photoanode and improves the light absorption efficiency. 1-x (ZnO) x The conduction band positions of the two are close, and it is not easy to form a high Schottky barrier at the interface, which facilitates the rapid transfer of photogenerated electrons. -2 Under simulated solar irradiation, the photocurrent density can reach 186μA·cm when the bias voltage is 1.23Vvs.RHE. -2 In addition, the preparation of the photoanode requires simple equipment, simple operation, and easy control of reaction parameters.

[0118] The above are only preferred embodiments of the present invention. It should be noted that all technicians in this technical field can make changes or modifications to this embodiment without departing from the spirit of the attached claims and the scope of the principles shown in the present invention, and these changes should also be regarded as the scope of protection of the present invention.

Claims

1. A CoPi-loaded dendrite (GaN) 1-x (ZnO) x -GaN nanowire array photoanode, characterized in that, CoPi loaded dendrite (GaN) 1-x (ZnO) x -GaN nanowire array photoanode uses n-type Si doped GaN single crystal with good conductivity as substrate, the main trunk is GaN nanowire array, and the branches are (GaN) 1-x (ZnO) x Solid solution nanowires, the solid solubility of ZnO is 19.4at%.

2. Dendritic (GaN) loaded with CoPi according to claim 1 1-x (ZnO) x -GaN nanowire array photoanode, characterized in that, The GaN substrate used is a Si-doped n-type GaN single crystal wafer prepared by MOCVD technology, with a film thickness of 4 to 6 μm and a sheet resistance of 14.08 kΩ / □.

3. Dendritic (GaN) loaded with CoPi according to claim 1 1-x (ZnO) x -GaN nanowire array photoanode, characterized in that, The GaN nanowire array material is epitaxially grown by chemical vapor deposition. The diameter of a single GaN nanowire is between 100 and 150 nm, and the length is between 10 and 25 μm.

4. Dendritic (GaN) loaded with CoPi according to claim 1 1-x (ZnO) x -GaN nanowire array photoanode, characterized in that, Dendrites grown on GaN nanowires (GaN) 1-x (ZnO) x The diameter of the solid solution nanowires is between 15 and 25 nm, and the length is between 200 and 300 nm.

5. Dendritic (GaN) loaded with CoPi according to claim 1 1-x (ZnO) x -GaN nanowire array photoanode, characterized in that, The photoanode exhibits a typical three-dimensional dendrite structure, with GaN nanowires grown on the trunk (GaN) 1-x (ZnO) x Solid solution nanowire branching, (GaN) 1-x (ZnO) x CoPi oxygen evolution co-catalyst supported on solid solution nanowire branches, (GaN) 1-x (ZnO) x Au particles are deposited on the top of the solid solution nanowire branches.

6. A CoPi-loaded dendritic (GaN) according to any one of claims 1 to 5 1-x (ZnO) x -A method for preparing a GaN nanowire array photoanode, characterized in that: The method is divided into four stages and includes the following steps: In the first stage, GaN nanowire arrays are grown on n-type Si-doped GaN single crystal wafers: (1) Weigh 30-50 mL of deionized water and pour it into a reactor, add 0.5-1.5 mL of 3-5 mg / mL HAuCl4 solution and 2-4 mL of methanol CH3OH and stir evenly; then place the n-type Si-doped GaN single crystal substrate into the obtained solution, evacuate the reactor, and irradiate the top of the substrate with a 300 W xenon lamp for 10-30 min; take it out and wash it with deionized water, and then blow dry it with high-purity N2; (2) Weigh gallium oxide Ga2O3 powder and evenly spread it on the bottom of the alumina porcelain boat, invert the substrate obtained in step (1) on top of the porcelain boat containing gallium oxide Ga2O3 powder, and place it in a single temperature zone tubular furnace; (3) The tubular furnace is evacuated to a vacuum state, and then Ar gas is introduced to normal pressure, with an Ar gas flow rate of 40 to 60 sccm; the tubular furnace is heated at a rate of 10 to 15°C / min, and when the temperature reaches 800 to 900°C, the Ar gas is turned off, and NH3 is introduced at a gas flow rate of 10 to 100 sccm; (4) When the tube furnace reaches the reaction temperature, the reaction is fully reacted and then naturally cooled to obtain a GaN nanowire array material with an n-type Si-doped GaN single crystal wafer as a substrate; The second stage is to prepare Zn-Ga-O precursor powder: (5) Weigh zinc acetate dihydrate Zn(CH3COO)2·2H2O and hydrated gallium nitrate Ga(NO3)3·xH2O, and place them in a 50 mL beaker, wherein the atomic ratio of Zn to Ga in the zinc acetate dihydrate and the hydrated gallium nitrate is 5:5, and the total weight of the powder is 4 to 6 g; (6) Add 15-25 mL of ethylene glycol methyl ether (C3H8O2) and 0.5-1.5 mL of ethanolamine (C2H7NO) to step (5), and stir until the powder is completely dissolved; (7) placing the solution obtained in step (6) in a water bath at 60-80° C. and stirring and heating for 5-7 h to obtain a sol, and then taking it out and letting it stand for one week to obtain a gel; (8) pouring the gel obtained in step (7) into an alumina porcelain boat and placing it in a single temperature zone tube furnace, and air annealing at 450-550° C. for 1.5-2.5 h to obtain a Zn—Ga—O precursor powder; The third stage is the growth of GaN nanowire arrays (GaN) 1-x (ZnO) x Solid solution nanowire branching: (9) Weigh 30-50 mL of deionized water and pour it into a reactor, add 0.5-1.5 mL of 3-5 mg / mL chloroauric acid HAuCl4 solution, 2-4 mL of methanol CH3OH and 8-12 mg of polyvinyl pyrrolidone PVP and stir evenly; then put the GaN nanowire array obtained in step (4) into the solution, evacuate the reactor, and irradiate the top of the reactor with a 300 W xenon lamp for 10-30 min; (10) Weigh the Zn—Ga—O precursor powder obtained in step (8) and place it in an alumina porcelain boat, and invert the sample obtained in step (9) on top of the porcelain boat containing the Zn—Ga—O precursor powder, and place it in a single temperature zone tubular furnace; (11) Before heating the tube furnace, purge the quartz tube with Ar gas for 20 to 40 minutes at a gas flow rate of 80 to 120 sccm, and then adjust the gas flow rate to 40 to 60 sccm; (12) The heating rate of the tubular furnace is 10-15°C / min. When the temperature reaches 700-750°C, the Ar gas is turned off and NH3 is introduced at a flow rate of 50-100 sccm; (13) When the tube furnace reaches the reaction temperature, it is kept warm for sufficient reaction and then cooled naturally to obtain dendritic (GaN) 1-x (ZnO) x / GaN nanowire array photoanode; The fourth stage, in (GaN) 1-x (ZnO) x / GaN nanowire array / CoPi oxygen evolution co-catalyst loaded on GaN by light-assisted electrodeposition: (14) preparing 80-120 mL of a phosphate buffer solution with a molar concentration of 0.05-0.15 M and a pH of 7, then adding 0.05-0.15 mL of a cobalt nitrate hexahydrate Co(NO3)2·6H2O solution with a molar concentration of 4-6 mM and stirring well, and pouring the mixture into the electrolytic cell; (15) The sample obtained in step (13) was used as the working electrode, the Pt sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. The CoPi was loaded by the constant current method, the current was set to -10 μA, the deposition time was 5 to 30 min, and 80 to 120 mW / cm was used during the deposition. 2 The light source irradiates the sample surface; (16) Take out the sample obtained in step (15), wash it with deionized water and dry it to obtain the dendritic (GaN) loaded with CoPi. 1-x (ZnO) x -GaN nanowire array photoanode.

7. Dendritic (GaN) loaded with CoPi according to claim 6 1-x (ZnO) x -A method for preparing a GaN nanowire array photoanode, characterized in that: In step (2), the mass of gallium oxide weighed is 0.5 to 1.0 g.

8. Dendritic (GaN) loaded with CoPi according to claim 6 1-x (ZnO) x -A method for preparing a GaN nanowire array photoanode, characterized in that: In step (4), the reaction temperature is 1000-1150° C. and the insulation time is 5-15 min.

9. Dendritic (GaN) loaded with CoPi according to claim 6 1-x (ZnO) x -A method for preparing a GaN nanowire array photoanode, characterized in that: In step (10), the Zn-Ga-O precursor powder is 0.4-0.6 g.

10. Dendritic (GaN) loaded with CoPi according to claim 6 1-x (ZnO) x -A method for preparing a GaN nanowire array photoanode, characterized in that: In step (13), the reaction temperature is 850-900° C. and the insulation time is 5-20 min.